2016
DOI: 10.1002/chem.201603331
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery by Controlling a Supramolecular Host–Guest Assembly with a Reversible Photoswitch

Abstract: The reversibly switchable trans-chalcone/flavylium photochromic system was successfully coupled to the complexation equilibrium of a drug-cucurbit[7]uril host-guest assembly. Hence, the phototriggered release of memantine under illumination at 366 nm was observed. The process can be partially reverted through a thermally activated back reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 58 publications
0
54
0
Order By: Relevance
“…Light is recognized as a superior stimulus for many applications because it allows for remote spatiotemporal control, it is orthogonal to other stimuli, and additional reagents are not required . Although different host–guest complexes formed from CBn and photoresponsive guests had been reported, most of them show binding affinities in the micromolar range or above . In particular, CB8 is known to simultaneously bind two anthracene derivatives in its cavity with high stability, accelerating their photodimerization.…”
Section: Methodsmentioning
confidence: 99%
“…Light is recognized as a superior stimulus for many applications because it allows for remote spatiotemporal control, it is orthogonal to other stimuli, and additional reagents are not required . Although different host–guest complexes formed from CBn and photoresponsive guests had been reported, most of them show binding affinities in the micromolar range or above . In particular, CB8 is known to simultaneously bind two anthracene derivatives in its cavity with high stability, accelerating their photodimerization.…”
Section: Methodsmentioning
confidence: 99%
“…[5] As presented by the same authors, irradiation of transchalcone 63 a (366 nm for one hour; solution pD = 4.4) triggers the slow formation of flavylium cation 63 b, which can then efficiently eject memantine (64) from the cavity of CB [7] (from 80 % to 10 % encapsulation). [108] Liu and Ma showed that acyclic CB[n] 65 (R = H, CH 3 ; negative at pH 7.4, see Scheme 9) can encapsulate a series of positively charged guests including berberine (6). [108] Liu and Ma showed that acyclic CB[n] 65 (R = H, CH 3 ; negative at pH 7.4, see Scheme 9) can encapsulate a series of positively charged guests including berberine (6).…”
Section: Guest Release and Capture Controlled By Ancillary Reactionsmentioning
confidence: 99%
“…[5,6] Hence it is not a surprise that organic molecules with protonable or peralkylated heteroatoms are preferred. In general high binding constants result, which are an additional asset for the widely recognized application potential of cucurbiturils in sensing and switching, [8][9][10][11][12][13][14][15] biomolecule modification, [4,[16][17][18][19] and delivery, [14,[20][21][22][23][24][25] to name just a few examples. [7] In some cases the complexation is also entropically favored.…”
Section: Introductionmentioning
confidence: 99%